PENGARUH KECERDASAN MATEMATIKA LOGIK PESERTA DIDIK TERHADAP KOMPETENSI EKSTERNAL MATEMATIKA SISWA - Hawa Liberna (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
Abstract This study aims to find out about the development of Logical Mathematical Intelligence Competency External Students to Math Students of SMA Muhammadiyah Sawangan Depok. The method used was a survey. The study population was all students of SMA Muhammadiyah Sawangan Depok. Samples were taken with a simple random sampling technique, a total of 37 students. Data were analyzed by regression analysis. The results of hypothesis testing showed that there are positive and significant influence on the logical mathematical intelligence external competence math students. Keywords: mathematics, intelligence, external capabilities